Intestinal Metaplasia of Antral Superficial-foveolar Epithelium in Children with Atrophic Gastritis - Natalia Yurievna Shirokova; Natalia Yurievna Orlinskaya; Diana Anatolyevna Davydova (Galenos Yayinevi, 2017)
Aim: Chronic gastritis (CG), being one of the most common digestive diseases, is frequently underestimated both by patients and clinicians. However, CG developed as early as in childhood, and often accompanied by Helicobacter pylori contamination of antral mucus, has a persistent recurrent course in adult patients, complicated by mucosal transformations in the form of atrophy, metaplasia and dysplasia. CG can appear as an early stage in the morphogenesis of tumor growth. From this point of view, CG is worth noticing. Materials and Methods: A complex morphological study of antral mucosa in school children with atrophic gastritis has been performed using histochemistry, immunohistochemistry and a morphometric methods. Results: In atrophic gastritis we have revealed the decrease in the number of functionally mature cells responsible for the production of extracellular matrix and basal membrane components, the lack of which in paraepithelial localization results in the change of their special properties. In addition, sulphomucins, non-characteristic of stomach, overlapped on mucosa and in single foveolae have been found in atrophic gastritis. Conclusion: Permanent impairment in the conjugation of cell and tissue components in mucosa accompanied by the change of an epithelial layer synthetic function with the impaired physicochemical properties of gastric mucin results in intestinal metaplasia as early as in childhood. Introduction